A metagenomic analysis coupled with oligotrophic enrichment approach for detecting specified microorganisms in potable groundwater samples - Daddy Gaoh, Soumana; Alusta, Pierre; Lee, Yong-Jin; Hussong, David; Marasa, Bernard; Ahn, Youngbeom (Frontiers in Microbiology, 2025)
In pharmaceutical manufacturing, there is a significant need for the detection and identification of specified microorganisms (i.e., Burkholderia cepacia complex (BCC), E. coli, Pseudomonas aeruginosa, Salmonella enterica, Staphylococcus aureus, Clostridium sporogenes, Candida albicans, and Mycoplasma), which are often missed or not identified by traditional culture-dependent methods. We employed a metagenomic analysis coupled with oligotrophic enrichment to identify specified microorganisms and evaluate tryptic soy broth (TSB) and 1/10 strength TSB for the recovery of specific microorganisms in potable groundwater samples. A total of 589–996 genera were identified in 12 water samples taken from a cold water fountain, with Bacillus spp. (97%) in TSB and Stenotrophomonas spp. (97%) in 1/10 strength TSB, representing the primary recovered genera after a 72-h pre-enrichment at 23°C. Likewise, we also detected lower abundance of specific organisms, Clostridium spp., Burkholderia spp., and Staphylococcus spp. (0.04–0.07%) in TSB and Burkholderia spp., Pseudomonas spp., Salmonella spp., Staphylococcus spp. and Escherichia spp. (0.01–1.73%) in 1/10 strength TSB. Co-inoculation with Burkholderia cepacia complex (BCC) yielded a higher recovery rate of Pseudomonas spp. compared to uninoculated controls in 1/10 strength TSB. Further functional analyses indicated that, toluene degradation (PWY-5180 and PWY-5182) was chiefly contributed by BCC in co-cultures of TSB + BCC-24 h and TSB + BCC-48 h. Our results demonstrate the potential value of the metagenomic approach during enrichment in detecting specified microorganisms, including oligotrophs such as BCC in non-sterile pharmaceutical products.